148 The Cost Effectiveness of Screening Young Athletes with ECG in The UK. (3rd June 2016) - Dhutia, Harshil; Malhotra, Aneil; Narain, Rajay; Merghani, Ahmed; Senior, Jon; Azizi, Saeed; Finnochiaro, Gherardo; Papadakis, Michael; Tome, Maite; Sharma, Sanjay
Abstract : Introduction: High false positive rates and subsequent costs of additional investigations provide major obstacles to state-sponsored screening of young athletes for cardiac disease with ECG. However, the actual cost of ECG screening in large cohorts of athletes has never been assessed systematically. We investigated the financial implications of ECG screening in young athletes in the UK, and evaluated the impact of modification of ECG interpretation criteria on cost. Methods: Between 2011–14, 4, 925 athletes (14–35 years) were consecutively assessed through a charity screening programme with history, physical examination and an ECG interpreted with the ESC criteria by a cardiologist at a cost of £35 per athlete. Athletes with abnormal results underwent additional tests at hospitals in their geographic vicinity at the discretion of the hospital cardiologist. The cost of additional tests were based on the UK National Health Service tariffs. A cost-projection model to evaluate cost-effectiveness was conducted based on (1) our costs, (2) UK sports participation statistics and (3) data from an Italian study which reported a 3.6/100, 000/years reduction in incidence of sudden cardiac death in athletes screened with ECG over 20 years (Figure 1 ). The Seattle and refined criteria for ECG interpretation were applied to the cohort retrospectively. Results: The majority of athletes were male (83%) and Caucasian (85%). 26 sports were represented. 1.6% had an abnormal history or physical examination. 21.8% had an abnormal ECG according to the ESC criteria. 11.2% athletes required echocardiography, 1.9% exercise testing, 1.4% holter, 1.2% cardiac MRI and 0.2% required other tests after 30 month follow-up. The Seattle and refined criteria reduced the abnormal ECG rate to 6% and 4.3% respectively. 15 athletes (0.3%) were identified with potentially sinister cardiac disease by all 3 criteria. Following further tests, the cost of screening with the ESC criteria amounted to £72 per athlete screened and £23, 750 per condition detected. The Seattle and refined criteria reduced costs to £61 and £58 per athlete respectively, and £20, 160 and £18, 976 per condition detected (Figure 2 ). 20 years of annual screening would save 1, 667 lives at a cost of £3.5 million per life saved with the ESC criteria; the Seattle and refined criteria reduced the cost to £3 million and £2.8 million per life saved respectively. Conclusions: The impressive 20% cost saving associated with ECG modification will be welcomed by organizations that mandate screening for their athletes. However, ECG screening is expensive considering the large number of young athletes that would require screening and the low event rate in such populations. Further ECG modification and physician education is required for such practices to be achievable or sustainable at a state-level.